Exposing The Fantasy Structure In All These Sunken Souls: Black Horror Anthology - Salsabilla, Annisya; Supsiadji, Mateus Rudi (Proceeding of Conference on Literature, Linguistic, and Cultural Studies, 2025)
The thesis entitled “Exposing the Fantasy Structure in All These Sunken Souls: Black Horror Anthology” aimed to reveal the fantasy story structure in the ten stories within the book All These Sunken Souls, published by Amberjack Publishing, and to classify those ten stories into Todorov’s three types of fantasy structures. The method used to analyse the ten short stories was a qualitative descriptive method with a literature study technique to collect data. This research applied Tzvetan Todorov’s narratology and fantasy theory. Both theories were utilized to uncover the fantasy story structure in the ten short stories in All These Sunken Souls, including the stages of equilibrium/initial situation, disruption/strange events, recognition/hesitation, repair/explanation, and new equilibrium/outcome. After analyzing the fantasy structure, the type of fantasy in each story was identified. The second analysis was carried out by examining the motifs and fantasy events appearing in each short story. Then, the writer grouped the stories into Todorov’s three types of fantasy structures: the Uncanny, the Marvelous, and the Pure Fantasy. Through this research, the result obtained was a depiction of the construction of the fantasy structure in All These Sunken Souls, which pointed to the types and categories of Todorov’s fantasy stories. The analysis revealed that out of the ten stories, only two types of Todorov’s fantasy structures were found: the Marvelous and the Pure Fantasy. The Uncanny type was not represented in any of the stories, which indicated a strong inclination toward supernatural and ambiguous elements rather than rational or psychological explanations.